Tafsir Kontekstual Qs. Al-Baqarah Ayat 178: Rekonstruksi Qishas dan Pemaafan dalam Perspektif Keadilan Restoratif di Indonesia - Samaun Samaun (Jurnal Pendidikan, Bahasa dan Budaya, 2026)
Al-Baqarah verse 178 regulates the legal mechanism of qishas as the maximum sanction for the criminal act of murder, while simultaneously opening space for forgiveness through the mechanisms of 'afwu and diyat. This verse is often understood partially and retributively, creating a negative impression of the Qur'an as merely emphasizing vengeance. This article re-examines the verse using a contextual tafsir approach to reconstruct an understanding of qishas that is not only retributive in dimension, but also restorative and humanistic. Employing the contextual tafsir method and the maqashid al-syari'ah approach, particularly hifz al-nafs as the primary objective of sharia, this study analyzes the semantic structure and asbab al-nuzul of the verse. The findings indicate that the phrase "fa man 'ufiya lahu min akhihi syai'un" emphatically affirms the Qur'an's priority on the preservation of life and social reconciliation over the execution of qishas. The term "akhihi" underscores fraternal relations as the basis for forgiveness. In the context of post-2023 Indonesia, following the enactment of the new Criminal Code that explicitly accommodates restorative justice, this verse offers a strong normative-theological foundation. Qishas is positioned as the maximum limit and ultimum remedium, while 'afwu and diyat become the main objectives for realizing justice that restores victim-perpetrator relations. Thus, the contextual interpretation of QS. Al-Baqarah: 178 is academically and practically relevant for supporting the implementation of restorative justice in Indonesia's criminal justice system without neglecting divine values.